Fundamental Financial Performance Analysis and Stock Valuation of PT DCI Indonesia TBK at Year 2024 - Mega Hermawan; Ana Noveria (Green Publisher Indonesia, 2025)
Indonesia’s accelerating digital transformation has boosted demand for data center services, positioning PT DCI Indonesia Tbk (DCII) as a key player. Since its IPO in 2021, DCII’s stock surged to IDR 42,100 by end-2024, raising concerns about whether this valuation reflects financial fundamentals or speculative sentiment. This study evaluates DCII’s intrinsic value using financial ratio analysis and valuation models. Financial performance shows strong profitability and revenue growth, yet liquidity weaknesses and longer collection periods signal emerging risks. A multi-stage Discounted Cash Flow (DCF) model projects free cash flow over 15 years, with a terminal growth rate of 4% and WACC of 12.85%, yielding a fair value of IDR 18,529 per share less than half of its market price. Comparable Company Analysis (CCA) further reveals that DCII trades at a significant premium across EV/EBITDA and P/E multiples. Sensitivity tests confirm intrinsic values consistently below market levels, suggesting investor expectations exceed fundamentals. The study recommends a 1:3 stock split with insider lock-up, quarterly investor bulletins, and working capital optimization to reduce mispricing and strengthen sustainability. Future research may extend to Southeast Asian peers and incorporate ESG and customer concentration factors.